Impaired DNA damage response signaling by FUS-NLS mutations leads to neurodegeneration and FUS aggregate formation - Naumann, Marcel; Pal, Arun; Goswami, Anand; Lojewski, Xenia; Japtok, Julia; Vehlow, Anne; Naujock, Maximilian; Günther, René; Jin, Mengmeng; Stanslowsky, Nancy; Reinhardt, Peter; Sterneckert, Jared; et al. (Nature Communications, 2018)
Amyotrophic lateral sclerosis (ALS) is the most frequent motor neuron disease. Cytoplasmic fused in sarcoma (FUS) aggregates are pathological hallmarks of FUS-ALS. Proper shuttling between the nucleus and cytoplasm is essential for physiological cell function. However, the initial event in the pathophysiology of FUS-ALS remains enigmatic. Using human induced pluripotent stem cell (hiPSCs)-derived motor neurons (MNs), we show that impairment of poly(ADP-ribose) polymerase (PARP)-dependent DNA damage response (DDR) signaling due to mutations in the FUS nuclear localization sequence (NLS) induces additional cytoplasmic FUS mislocalization which in turn results in neurodegeneration and FUS aggregate formation. Our work suggests that a key pathophysiologic event in ALS is upstream of aggregate formation. Targeting DDR signaling could lead to novel therapeutic routes for ameliorating ALS.
Gesehen am 16.06.2021